2019
DOI: 10.5817/cp2019-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Passive social networking site use and well-being: The mediating roles of social comparison and the fear of missing out

Abstract: Passive social networking site use and well-being: The mediating roles of social comparison and the fear of missing out. AbstractPassively browsing social networking sites (SNSs) correlates with poorer well-being (Verduyn, Ybarra, Résibois, Jonides, & Kross, 2017). However, less research has been conducted that fully examines what factors may mediate this association. In particular, both online social comparison and the fear of missing out (FoMO) may play roles in how passive SNS browsing relates to depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 41 publications
6
73
0
2
Order By: Relevance
“…Perhaps due to the high visuality and positive self-presentation tendencies of SNSs (Vogel and Rose, 2016), passive SNS browsing, as a whole, is linked to poorer well-being, including greater depressed mood Eggermont, 2016, 2017, for girls only;Escobar-Viera et al, 2018;Burnell et al, 2019;Thorisdottir et al, 2019;but see Beyens et al, 2020) and loneliness (Frison and Eggermont, 2020). Experimental studies in which participants browse content preselected by the researchers (which usually exemplifies especially highly positive self-presentation) have found that Instagram browsing can decrease positive mood, particularly for those who are likely to compare themselves to this content (Weinstein, 2017;de Vries et al, 2018), and can also increase negative mood (Brown and Tiggemann, 2016;Weinstein, 2017).…”
Section: Browsing Others' Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps due to the high visuality and positive self-presentation tendencies of SNSs (Vogel and Rose, 2016), passive SNS browsing, as a whole, is linked to poorer well-being, including greater depressed mood Eggermont, 2016, 2017, for girls only;Escobar-Viera et al, 2018;Burnell et al, 2019;Thorisdottir et al, 2019;but see Beyens et al, 2020) and loneliness (Frison and Eggermont, 2020). Experimental studies in which participants browse content preselected by the researchers (which usually exemplifies especially highly positive self-presentation) have found that Instagram browsing can decrease positive mood, particularly for those who are likely to compare themselves to this content (Weinstein, 2017;de Vries et al, 2018), and can also increase negative mood (Brown and Tiggemann, 2016;Weinstein, 2017).…”
Section: Browsing Others' Profilesmentioning
confidence: 99%
“…FoMO is conceptualized as experiencing anxiety over others potentially having more rewarding experiences than the self (Przybylski et al, 2013), and is linked to greater SNS use and poorer wellbeing (Przybylski et al, 2013;Baker et al, 2016;Blackwell et al, 2017;Buglass et al, 2017;Roberts and David, 2019). FoMO inherently requires some degree of upward social comparison, as a necessary component is perceiving that others are doing better than the self (Burnell et al, 2019;Reer et al, 2019). For emerging adults who are experiencing identity development, they may experience greater comparison processes such as FoMO to better assess the self.…”
Section: Individual Differencesmentioning
confidence: 99%
“…SNSs can provide individuals experiencing loneliness and emotional instability with social support but higher stress levels resulting from a social comparison orientation toward other SNS users (Berezan et al 2020;Lo et al 2018). Passive SNS usage (e.g., direct or indirect content consumption of others' idealized SNS profiles, pictures, and status updates) is closely related to social comparison orientation, which reduces social capital and subjective well-being (Burnell et al 2019;Lin et al 2018;Liu et al 2018). Therefore, the following hypothesis is proposed: H1: Social comparison orientation will have a direct negative effect on psychological well-being.…”
Section: Independent Variable: Social Comparison Orientationmentioning
confidence: 99%
“…Specifically, Facebook use predicts upward social comparison, which negatively influences individuals' self-esteem and well-being over time, whereas Instagram use has a direct negative effect on psychological well-being (Schmuck et al 2019). SNS use is a strong predictor of social comparison, which is positively related to the fear of missing out and depressive symptoms through rumination and negatively related to global self-worth, self-perceived physical appearance, and self-perceived social acceptance (Burnell et al 2019;Feinstein et al 2013). Individuals with greater social comparison orientation derived from low self-esteem have worse mental health, as they are more likely to hurt themselves psychologically (Jang et al 2016).…”
mentioning
confidence: 99%
“…The fear-of-missing-out (FoMO) construct seems to be a potential mediating factor. Several studies illustrated the importance of FoMO as a risk factor of problematic social networks use [61][62][63][64][65][66][67][68][69]. Furthermore, FoMO mediated the effect of specific predisposing variables (e.g., interpersonal sensitivity, depression, social anxiety, self-esteem) on tendencies of social networks use disorder [65,66,70,71].…”
Section: Empirical Overview About Psychosocial Characteristics As Rismentioning
confidence: 99%